english english - Maulida, De Lara Siti; Saehu, Andang (BASIS (Bahasa dan Sastra Inggris), 2022)
Regarding the requirement of incorporating ICT competences into the teaching and learning process, the aim of this research is to design Models of Teaching for Writing Courses that have infused ICT competences into its teaching and learning activities. R&D was used and adapted from Richey and Klein's concept, with four stages of research including Need Analysis, Design Preliminary Product, Evaluation, and Revision. Literature study and observation were required during the design of ICT competences-integrated teaching models. The findings revealed that integrating ICT competences into existing teaching models was as knowledge deepening as the dominant ICT competences level in which students performed the ability to manage information and used open-ended software tools to access information, deliver the material, and collaborate with peers. Meanwhile, Kilbane and Milman's integrative teaching models were modified, and ICT was incorporated into the design of the Teaching Model for the Writing Course, which was reflected as a prototype lesson plan outlined in paragraphs.